Conceptual thinking from the Western and Islamic perspectives. - Abdullah, Norillah; Badi, Jamal Ahmed Bashier; Mat Ali, Siti Nazilah (IIUM Press, International Islamic University Malaysia, 2021)
This paper examines the concept of thinking from the worldviews of the Western and Islam by highlighting the ideological differences. Thinking from a Western viewpoint involves just the body and mind which is described as the ability to analyse arguments, draw conclusions through reasoning, make judgments and assessments, evaluate circumstances, and find a solution to a problem. Meanwhile, thinking from an Islamic perspective involves not only the body and mind but also the spiritual aspect of qalb, aql, and nafs. This study is a library based research and it employs qualitative data analysis. Methodology used is based on descriptive, comparative, evaluative and critical analysis from both perspectives. A comparison is made between the two notions and the implications of both. A theoretical model of thinking which is based on Islamic worldviews is also proposed.